ANALYSIS OF THE QUALITY OF PUBLIC SERVICES IN DPPPAKB PASURUAN CITY THE APPLICATION OF SERFING LEADERSHIP SATYLES IN THE SUB-DICTRICT OFFICE DULUPI KABUPATEN BOALEMO - Hesti Musa1; Imam Mashudi; Sitti Husna (Journal of Governance and Global Studies, 2024)
This study aims to determine the style of serving leadership in the Dulupi District Office, Boalemo Regency. The method in this study uses descriptive qualitative methods with data collection techniques by observation, interviews and documentation. The results of the study show that the leadership style in the Dulupi sub-district office has not been implemented properly, so there are still things that are lacking and need to be improved and developed again. This can be seen from the various characteristics of servant leadership that need to be improved and further developed, namely listening, empathy, predictability, healing ability and serving ability. Therefore, the characteristics of leadership need to be improved and developed again. Good characteristics in government, because the presence of leader characteristics can make employees grow in working well in the work environment and government. The leader is an exemplary example and can provide direction and therefore can create a sense of enthusiasm and openness, so that teamwork can work well and correctly to achieve common goals.